Molecular-Mass Distribution of Peptides in the Extracts of Cryopreserved Fragments from Pig Spleen and Piglet Skin - Bespalova, Irina G.; Rohoza, Liliya A. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Â Probl Cryobiol Cryomed 2014; 24(2):167. Â Â